Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4028/www.scientific.net/amr.779-780.1600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on Adsorption and Removal of Antimony from Acidic Aqueous Solution by Activated Carbons and Machine-Made Charcoal

Abstract: Adsorption effects of three kinds of activated carbons and a type of machine-made charcoal on the removal of antimony from acidic aqueous solution were investigated and compared. With an initial antimony solution concentration of 1000 μgL-1, the antimony adsorption by selected adsorbents were found to descend in the following order: machine-made charcoal (52.4%) > coconut activated carbon (42.6%) > coal based activated carbon (31.1%) > apricot stone based activated carbon (24.6%). The machine-made cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…A number of experiments and model studies of the adsorption of arsenic and other heavy metals are described in various publications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These studies describe sorption processes at different pH values, initial heavy metal ion concentrations in water, solid/liquid ratio, particle size of a sorption material, filtration rate, temperature and composition of water to be treated (concentration of iron, manganese, phosphorus, silicon, fluorides, sulphates, organic matter, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments and model studies of the adsorption of arsenic and other heavy metals are described in various publications [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. These studies describe sorption processes at different pH values, initial heavy metal ion concentrations in water, solid/liquid ratio, particle size of a sorption material, filtration rate, temperature and composition of water to be treated (concentration of iron, manganese, phosphorus, silicon, fluorides, sulphates, organic matter, etc.…”
Section: Introductionmentioning
confidence: 99%
“…S1 †), and this supported the reduction of Cu(II) to that with lower chemical valence, i.e., Cu 0 , Cu I . Furthermore, the thermodynamic calculation also indicated that Sb(III) may be oxidized to Sb(V) by Cu II , and the possible chemical reactions eqn (11) and (12) are given as follows: 3 as the main Sb(III) species at pH 7.0 (Fig. S3 †).…”
Section: Proposed Mechanism Of Sb(iii) and Sb(v) Adsorptionmentioning
confidence: 98%
“…It is widely considered as one of the best available technologies for medium-and smallscale systems. 10 Conventional adsorbents such as activated carbon, 11 aluminum-based adsorbent, 12 and iron-based adsorbent 13 have been developed for Sb adsorption. However, their adsorptive capacity is not as high as expected, and the high operating costs of solid-liquid separation process which hinders their large-scale applications.…”
mentioning
confidence: 99%